Young Fatal Case of Familial Hypercholesterolemia: A Case Report - Hakim Irfan Showkat; Sadaf Anwar; Vinod Sharma; Sanjeev Asotra (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Familial hypercholesterolemia (FH) is a genetic disease presented by high levels of serum low density lipoprotein (LDL), xanthomas and early coronary artery disease (CAD). The main cause of FH is LDL receptor abnormalities that decrease the uptake of LDL into cells, particularly into the liver cells, from the blood, resulting in the increase of serum LDLcholesterol levels.